UWSim, an underwater robotic simulator on the cloud as educational tool - Javier Pérez; David Fornas; Raúl Marín; Pedro J. Sanz (Revista Iberoamericana de Automática e Informática Industrial RIAI)
Due to the introduction of robotic applications in the modern society, such as service robots or self-driving cars, it is possible to use this trend as motivating factor in the learning process of robotics. Several possibilities about how to use this motivation to increase learning rate are analysed, focusing on underwater robotic simulators. Moreover, a cloud learning environment able to evaluate the students with a robotic simulator is proposed as key element of the system. These kinds of tools can be used with just an Internet-capable system through a web browser, reaching a virtually unlimited amount of resources. The implemented features are used in a underwater pipe following application, creating a comparison environment on the cloud that immerse students in a competition to reach the best possible result. Finally, a first experience in a real educational environment using the proposed tool is detailed, demonstrating the viability and suitability of the proposed tool.